Backstepping Controller for Electrically Driven Flexible Joint Manipulator Under Uncertainties - Lilia Zouari; Hafedh Abid; Mohamed Abid (Institute of Advanced Engineering and Science, 2015)
The grown complexity of the robot manipulators dynamics taking into account the jointflexibility, parameter uncertainties and unknown bounded disturbances makes conventionalcontrol strategies difficult and complex to synthesize. This paper focuses on the investiga-tion into backstepping control of flexible joint manipulator driving by Brushless DC Motor(BDCM) in the presence of parameter uncertainties and unknown bounded disturbances fortracking trajectory. The goal of this paper is to compensate all uncertainties and distur-bances for flexible joint manipulator. To study the effectiveness of the controllers, backstep-ping controller has been developed for position control and an hysteresis controller has beentreated for current control. Simulation results of the response of the flexible joint manipu-lators associated with their controllers have been presented. The high performances of thebackstepping control are examined in terms of tracking accuracy and error reduction.